1985
DOI: 10.1177/003754978504500202
|View full text |Cite
|
Sign up to set email alerts
|

Just-In-Time (JIT), with Kanban, manufacturing system simulation on a microcomputer

Abstract: A simulation model of a Just-In-Time (JIT) manufacturing system using a two-card and a one-card Kanban inventory control system has been developed using the SIMAN simulation language on the IBM microcomputer. The manufacturing system consists of an assembly line with two assembly cells, one manufacturing cell, and one incoming receiving cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Earlier on, research about TPS consisted of descriptions on specific tools and techniques, such as Just-in-Time (JIT) and Kanban (Monden, 1983;Schonberger, 1982;Schroer et al, 1985;Sugimori et al, 1977), Jidoka (Monden, 1983;Ohno, 1988;Pegels, 1984;Sugimori et al, 1977), and Single-Minute Exchange of Dies (SMED) (Shingo and Dillon, 1989), but none of them considered the whole management system at Toyota (Holweg, 2007). Therefore, Womack et al (1990) set a starting point for viewing Lean as a concept, and the research has continued to develop the knowledge of the principles and practices behind Toyota's success.…”
Section: Lean Productionmentioning
confidence: 99%
“…Earlier on, research about TPS consisted of descriptions on specific tools and techniques, such as Just-in-Time (JIT) and Kanban (Monden, 1983;Schonberger, 1982;Schroer et al, 1985;Sugimori et al, 1977), Jidoka (Monden, 1983;Ohno, 1988;Pegels, 1984;Sugimori et al, 1977), and Single-Minute Exchange of Dies (SMED) (Shingo and Dillon, 1989), but none of them considered the whole management system at Toyota (Holweg, 2007). Therefore, Womack et al (1990) set a starting point for viewing Lean as a concept, and the research has continued to develop the knowledge of the principles and practices behind Toyota's success.…”
Section: Lean Productionmentioning
confidence: 99%
“…Kimura and Terada (1981) showed that, compared with a 'push' system, a 'pull' production line reduces the amplification of production and inventory fluctuations when order quantity and lead times ani small. Schroer et al (1985) developed a microcomputer simulation model of a manufacturing system, composed of an assembly line, two assembly cells, one manufacturing cell and one incoming receiving cell. The main objectives were to balance the system in terms of resources and queues and to minimize in-process inventory at the various stock points.…”
Section: Introductionmentioning
confidence: 99%
“…We have used the Petri net modeling on other Kanban systems encountered in the literature, and most of the Petri net models we obtained were very similar to the basic one. That is the case with the models of Huang, Rees, and Taylor (1983) ;Schroer, Black, and Zhang (1985); Bitran and Chang (1987); Lulu and Black (1987); and Suri and de Treville (1987). Some authors considered Kanban systems that have a rather different behavior than those we have just seen.…”
Section: Classical Kanban Systemsmentioning
confidence: 99%
“…Recently, much work has been devoted to this problem. Authors often use simulation models to evaluate the performance (see, for example, Huang et al, 1983;Schroer et al, 1985;Lulu and Black, 1987). Some analytical methods have also been developed.…”
Section: Introductionmentioning
confidence: 99%